The grape rootworm, Fidia viticida (Coleoptera: Chrysomelidae), newly recorded from Quebec - Vincent, Charles; Dumont, Stéphane; de Tonnancour, Pierre (Phytoprotection, 2017)
The occurrence of the North American native grape rootworm, Fidia viticida Walsh (Coleoptera: Chrysomelidae), is reported for the first time in Quebec. During the summer of 2016, adults were beaten from Virginia creeper, Parthenocissus quinquefolia, and riverbank grape, Vitis riparia, along the Papineau-Leblanc Highway in Laval, Quebec. Fidia viticida is a pest of cultivated grapes in the Lake Erie area. Its current pest status in Canada is unknown.